Numerical investigation of entropy generation due to Joule heating in the thermally stratified flow of MHD Powell-Eyring fluid towards a porous curved surface - Babu, P. R. Sobhana; Rao, D. Srinivasa; Waini, Iskandar; Sudarmozhi, K.; Kumar, A. Kiran; Jayalakshmi, P.; İnç, Mustafa (Elsevier, 2026)
Numerical simulation was utilised to evaluate entropy generation and the thermo-hydrodynamic behaviour of the unsteady magnetised Mg-Fe3O4 hybrid Powell-Eyring nanofluid flow over a porous, thermally stratified, curved surface, in relation to thermal engineering case studies. This study seeks to understand the interactions among flow stability, heat transfer, and entropy generation, considering the effects of magnetic field strength, viscous dissipation, Joule heating, the porous medium's resistance, and buoyancy forces from the surroundings. The Keller-Box Method was then applied to solve the coupled, nonlinear boundary-layer equations, thereby building confidence in the velocity, temperature, and concentration profiles, which were thoroughly validated against established benchmark studies. The findings showed that, together with the porous medium and magnetic field factors, these factors reduce the flow velocity and increase the temperature gradients and entropy generation, revealing essential consequences for the system's energy efficiency. The hybrid nanoparticles' superior thermal-conducting and flowstabilising effects around curved biomedical and microfluidic surfaces were observed. The characteristically advanced, multifaceted integration of physical effects is a step forward in the geted drug delivery, and progressive cooling as advanced cooling aids.
Keywords: Mixed convection; Joule heating; Viscous dissipation; Unsteady flow